New Mono- and Biaccelerator Iterative Methods with Memory for Nonlinear Equations. (23rd July 2014) - Lotfi, T.; Soleymani, F.; Shateyi, S.; Assari, P.; Haghani, F. Khaksar
Abstract : Acceleration of convergence is discussed for some families of iterative methods in order to solve scalar nonlinear equations. In fact, we construct mono- and biparametric methods with memory and study their orders. It is shown that the convergence orders 12 and 14 can be attained using only 4 functional evaluations, which provides high computational efficiency indices. Some illustrations will also be given to reverify the theoretical discussions.